2020
DOI: 10.1093/jme/tjaa050
|View full text |Cite
|
Sign up to set email alerts
|

Sand Fly (Diptera: Psychodidae) Species Diversity, Habitat Preferences, and Ecological Aspects of Distribution in Bajaur District, Khyber Pakhtunkhwa, Pakistan

Abstract: The species composition, distribution, and bionomics of sand flies was investigated from January to December 2017 in four tehsils (20 villages) of district Bajaur (formally Bajaur agency), Khyber Pakhtunkhwa, Pakistan. In total, 4,173 adult specimens comprising of seven species of Phlebotomus (Diptera: Psychodidae) and three species of Sergentomyia (Diptera: Psychodidae) were collected by oral aspirator, insecticide spray, and sticky traps from June to October. Highest numbers of flies were collected indoors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…• The outcomes of the study are vital to the effective and targeted control of CL in Mardan were identified by examining their external genitalia, which exhibit distinct characteristics of immaturity (Wahid et al, 2020). In the field, sand fly coordinate data were acquired using a global positioning system (GPS) device.…”
Section: Impactmentioning
confidence: 99%
“…• The outcomes of the study are vital to the effective and targeted control of CL in Mardan were identified by examining their external genitalia, which exhibit distinct characteristics of immaturity (Wahid et al, 2020). In the field, sand fly coordinate data were acquired using a global positioning system (GPS) device.…”
Section: Impactmentioning
confidence: 99%
“…Adult sand flies were collected on monthly and weekly basis. Monthly collections were made to define sand fly seasonal abundance (Khan, Llewellyn, et al, 2017) in the region, while weekly collections were performed to detect potential breeding sites (Wahid et al, 2020). Monthly collections were carried out in six indoor sites (including buffalo shed, cow shed, goat shed, sheep shed, cattle shed, and domestic household) from June to September 2019.…”
Section: Study Design and Sand Fly Collectionmentioning
confidence: 99%
“…Immature male sand flies were identified on the basis of their unrotated external genitalia (Khan, Llewellyn, et al, 2017;Moncaz et al, 2012b;Wahid et al, 2020).…”
Section: Study Design and Sand Fly Collectionmentioning
confidence: 99%
“…The study was conducted on the farmland and rainfed croplands in district Bajaur (34⁰44.161 N, 71⁰31.631 E), 850-1100 m elevation above mean sea level, covering an area of 1290 km 2 [17][18][19] (Fig. 1).…”
Section: Study Areamentioning
confidence: 99%